The Perfect Search Engine Is Not Enough: A Study of Orienteering Behavior in Directed Search - Teevan, Jaime; Alvarado, Christine; Ackerman, Mark S.; Karger, David R. (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI 2004), Vienna, Austria, 2004)
This paper presents a modified diary study that investigated how people performed personally motivated searches in their email, in their files, and on the Web. Although earlier studies of directed search focused on keyword search, most of the search behavior we observed did not involve keyword search. Instead of jumping directly to their information target using keywords, our participants navigated to their target with small, local steps using their contextual knowledge as a guide, even when they knew exactly what they were looking for in advance. This stepping behavior was especially common for participants with unstructured information organization. The observed advantages of searching by taking small steps include that it allowed users to specify less of their information need and provided a context in which to understand their results. We discuss the implications of such advantages for the design of personal information management tools.